2017
DOI: 10.1007/s41465-017-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Challenges of Implementing Motivational Features to Boost Cognitive Training Outcome

Abstract: In the current literature, there are a number of cognitive training studies that use N-back tasks as their training vehicle; however, the interventions are often bland, and many studies suffer from considerable attrition rates. An increasingly common approach to increase participant engagement has been the implementation of motivational features in training tasks; yet, the effects of such “gamification” on learning have been inconsistent. To shed more light on those issues, here, we report the results of a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Nine variants of the N-Back task were obtained by crossing three task structures (see below) with three stimulus types : words (i.e., so, do, up), pictures (i.e., apple, fish, and bag), and colors (i.e., red, green, and blue). Task structures differed in terms of stimulus duration, ISI, response contingency, and feedback (see Figure 1 ) and were modeled after tasks used in previous studies, as mentioned above: task 1 (Pahor and Jaušovec, 2018 ), task 2 (Pergher et al, 2018 ), and task 3 (Mohammed et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nine variants of the N-Back task were obtained by crossing three task structures (see below) with three stimulus types : words (i.e., so, do, up), pictures (i.e., apple, fish, and bag), and colors (i.e., red, green, and blue). Task structures differed in terms of stimulus duration, ISI, response contingency, and feedback (see Figure 1 ) and were modeled after tasks used in previous studies, as mentioned above: task 1 (Pahor and Jaušovec, 2018 ), task 2 (Pergher et al, 2018 ), and task 3 (Mohammed et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…In these training programs, task difficulty is adaptively adjusted based on performance. The main difference between the two training programs is the game environment: Recall is a 3D space-themed game (video demo can be found here: https://www.youtube.com/watch?v=zx_t6paHB3Y ) in which the participant is in control of a spaceship (Deveau et al, 2015 ; Mohammed et al, 2017 ). The participant must zap target stimuli while also collecting fuel pods for the space ship (non-targets).…”
Section: Methodsmentioning
confidence: 99%
“…(Middle) Example for a two-back level in the gamified Recollect condition. (Bottom) Example for a two-back level in the gamified Recall condition (Mohammed et al, 2017). each, with 2 sessions conducted per day with a 10 min break between sequential sessions.…”
Section: Participantsmentioning
confidence: 99%
“…Focusing specifically on motivational effects related to the training environment, Mohammed et al (2017) compared the effects of four weeks of training on a gamified working-memory training (a 3D space-themed "collection" game; Deveau et al, 2015) to working-memory training without motivational features. Participants in the game-training group reported that they enjoyed the intervention more and exerted more effort than the group who trained on the basic version.…”
mentioning
confidence: 99%
“…Most of the studies referenced above were primarily interested in the investigation of underlying mechanisms and individual differences, and thus, it is maybe not surprising that very few of them included any outcome measures that might reflect real-world performance (but see Hering et al, 2017, Mohammed et al, 2017, and Ralph et al, 2017). Nonetheless, given the common assumption that cognitive training approaches are broadly beneficial, it would be valuable if researchers would routinely include measures that serve at least as proxies for everyday life.…”
mentioning
confidence: 99%